Improving Students' Citizens Education Learning Outcomes About Pride as Children of Indonesia Through the Direct Learning Model - Djasni, Djasni (International Journal of Management and Education in Human Development, 2021)
The purpose of this study was to find out the description of Civic Education learning to improve student learning outcomes. To know the factors that Citizenship Education applied by the teachers of the Negeri Elementary School 2 Kendari. Knowing the learning strategies used by public elementary school teachers 2 Kendari in improving learning outcomes Citizenship Education about Pride as Children of Indonesia through direct learning model (model of direct instruction) in the academic year 2019/2020. The design of classroom action research procedures carried out in this study is a spiral or cycle learning model, according to Stephen Kemmis and MC, Taggaret. With found deficiencies, planning and implementation of improvements can still be in the next cycle until the desired target is achieved. The Kemmis model design has four stages in each cycle, namely: 1) making an action plan, 2) carrying out the action, 3) making observations or observations, 4) conducting reflection and evaluation. The Direct Instruction model is proven to improve student learning outcomes in creative writing. The data obtained in this study are: the first cycle of the PBI study of students reached 66.67%, the acquisition of post-test was 55.17%. The second cycle of the PBI study of students reached 76.19% while the post-test was 62.07%. The results obtained have met the success criteria set at the beginning of the study. Thus, based on the discussion of the research results that have been carried out, it can be concluded that the Direct Instruction Model can improve the quality of the Citizenship Education learning process as indicated by the increasing Citizenship Education learning outcomes test about Pride as Indonesian Children. There is a relationship between learning success and the achievement of learning operational steps designed in classroom action research conducted by researchers.